Malaysian Chinese New Year dishes nomenclature - Ng, Man Ling; Ang, Lay Hoon; Lam, Kai Chee (Malaysian Association of Modern Languages, 2015)
The Chinese people are generally very particular in the naming of the dishes served at restaurants. For the Chinese, dish naming is a knowledge involving the combination of the dishes’ ingredients together with their names to ensure that the names given can fit the specialty of the dishes and also maintain their uniqueness at the same time. This paper explains the nomenclature of Malaysian Chinese New Year dishes and investigates the impact the Chinese culture has on it. Malaysian Chinese dishes are normally named based on three methods, which consider the ingredients used (Realistic Nomenclature), cultural implication (Impressionistic Nomenclature), or a combination of both (The Actual Situation Nomenclature). A literature review revealed that a majority of the Malaysian restaurants tend to name the dishes by highlighting the cultural implication of the dishes. In this study, a total of 295 dishes were collected from 24 restaurants to classify the name of the dishes according to the three methods. The analysis revealed that dishes nomenclature in Malaysia is complex. Most of the Chinese New Year dishes are named according to cultural implication because Chinese people believe that a given good name will affect the year’s fortune.